The intersection of work and family life The role of affect.[article]. - Eby, Lillian T.
This review examines the role that trait-based and state-based affect plays in understanding the intersection of work and family life. We start with the definition of key terms and concepts. This is followed by a historical overview of the two bodies of scholarship that are the focus of this review, the work-family interface and affect. Next, we provide a review and synthesis of 79 empirical studies examining affect in relation to work-family interaction, organized around three perspectives: the disposal perspective, the state-based specific affective reactions perspective, and the state-based global affective reactions perspective. A methodological critique of these studies follows, providing a springboard for the discussion of recommended methodologies and data analytic approaches, along with directions for future research.